Identifying the role of Ni and Fe in Ni–Fe co-doped orthorhombic CoSe2 for driving enhanced electrocatalytic activity for oxygen evolution reaction. (1st March 2020) - Tuo, Yongxiao; Wang, Xueyuan; Chen, Chen; Feng, Xiang; Liu, Zhengqing; Zhou, Yan; Zhang, Jun
Abstract: Exploring the origin of high electrocatalytic activity of Ni–Fe–Co ternary selenides for oxygen evolution reaction (OER) is of fundamental importance for rational design of efficient electrocatalysts. In this report, we synthesize self-assembled microspheres by orthorhombic CoSe2 nanorods along with the Ni and/or Fe doped counterparts, and systematically investigate their electrocatalytic performance. The results show that, although either Ni-doping or Fe-doping can significantly enhance the catalytic activity of CoSe2, the ways they promote catalytic activity are different. The Tafel analysis demonstrates that Fe incorporation leads to a kinetics change in the OER while Ni incorporation has little effect. Based on the electrochemical characterizations and theoretical calculations, Ni-doping maintains Co active sites and does not alter the OER mechanism, but decreases the energy barrier of the rate-limiting step by modifying Co active sites. In contrast, Fe-doping transforms the active sites from Co to Fe, and the rate-limiting step changes to the O–OH formation stage, thus affording faster reaction kinetics. These findings are further confirmed by more Ni–Fe co-doped CoSe2 with various content of Ni and Fe. Specifically, under the optimal experimental conditions, Ni–Fe co-doped CoSe2 (Ni0.04 Fe0.16 Co0.8 Se2 ) exhibits a remarkable OER activity with an overpotential of ∼230 mV at 10 mA cm −2 and Tafel slope of 39 mV dec −1 . Graphical abstract: Image 1 Highlights: Ni, Fe doped CoSe2 with self-assembled microsphere structure was prepared for OER. The role of Ni and Fe dopants for enhancing OER activity has been investigated. Ni decreases the energy barrier of rate-limiting step by modifying Co active sites. Fe modulates the reaction kinetics by altering the rate-limiting step. Ni0.04 Fe0.16 Co0.8 Se2 offered a superior electro-catalytic OER activity.